Peningkatan Pengetahuan Ibu Tentang Pertumbuhan Gigi untuk Mencegah Kasus Persistensi pada Anak Usia 7-12 Tahun di Kecamatan Rappocini Kota Makassar - Zahrawi Astrie Ahkam; Amirah Maritsa; Hasrini Hasrini; Pariati Pariati; Zulkarnain Zulkarnain (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2022)
Children's dental health is an important aspect that needs special attention from parents, especially mothers, as the primary caregivers. Tooth growth in children aged 7-12 years is a crucial period where permanent teeth begin to replace milk teeth. However, mothers' ignorance or lack of knowledge about this process can lead to cases of persistence, which is when milk teeth remain in the oral cavity even though permanent teeth have begun to grow. This condition can cause various dental and oral health problems in children. This Community Service Program aims to increase mothers' knowledge about tooth growth and the importance of preventing cases of persistence in children in Rappocini District, Makassar City. The methods used include socialization and health education, accompanied by the distribution of educational materials and interactive discussions. The expected results of this activity are increased understanding of mothers regarding the stages of children's tooth growth, early signs of persistence, and preventive measures that can be taken at home. Thus, it is hoped that the number of cases of persistence in this area can be reduced, and children's dental health can be better maintained.